Exploring the Factors in Student’s Retention of E-learning Mathematics: A Case of Grade 12 Senior High School Students at the University of Perpetual Help System-Pueblo de Panay Campus - Ace N. Bombaes; Jeric S. Fuasan; Winston N. Garcia (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2021)
The study aims to determine the effects of teacher’s factors, student attitude, and motivation on student’s ability to absorb, recall and maintain the learned concepts. This research measures the effects of the said factors on student’s mathematics retention. For this study, the data are collected from 101 STEM students of the University of Perpetual Help System-Pueblo de Panay Campus. The data analysis is done using Paired t-test, Cronbach’s Alpha and Pearson r. The results have revealed that teacher’s factor, students’ attitude and motivation have significant differences. Results indicate that the three factors have statistical effect and significant impact on student's ability to absorb, recall and maintain the learned concepts in Mathematics via e-learning platform. Based on the findings, teacher’s factor is one of the factors the school should give much focus on since teacher has the ability to motivate and influence the attitude and performance of the students and they are accountable for the performance for the students. Furthermore, the study finds out that e-learning does not reduce education. Retention rates for online students are much higher than for traditional because it makes every learning material accessible, thus increasing student’s productivity by finishing a course when physical limitations are removed.